Co-production and the issue of urban up-scaling and governance change in the global south: The case of Uganda. (August 2022) - Siame, Gilbert; Watson, Vanessa
Co-production has emerged as a prominent strategy for producing urban spaces, delivering urban services and improving governance in poor but rapidly growing cities of the South. In the field of planning, it has been put forward as a more appropriate approach to what has generally been termed 'public participation': a term with its roots in the concept of collaborative planning emerging largely from experience in advanced economies of the West. Co-production has been used in several specific cases to build state-society alliances for community change and socio-spatial transformation. This paper argues that the transformative potential of the co-production approach lies in its ability to drive change at local, city-wide and trans-local scales. We argue that the capacity and ability to institutionalise and scale-up co-production activities depend on the ability of state and society locating and securing their 'locus standi' through political alignment, conflict resolution, political negotiations and collaboration. The paper contributes to literature in co-production and planning by analysing how the state and society use multiple tactics to achieve both collaboration and resistance as means of creating and sustaining a governance middle ground.